Structure failure analysis on metro axle-box hanger due to modal resonance with rail corrugation - Wenbiao Huo; Pingbo Wu; Qunsheng Wang; Lai Wei; Kang Wang; Shidong Wu (Advances in Mechanical Engineering, 2023)
During the long-term service of a metro vehicle, different kinds of fracture failure occur on the bogie, with the axle-box hanger being a representative one. To investigate the cause of the hanger structure failure, a study was conducted that combined field investigation with finite element analysis, focusing on the modal resonance behavior between the hanger and the rail corrugation. Based on the findings, a structural optimization of the hanger was proposed and an experimental verification was conducted. The results show that the main reason for the hanger fracture failure is that the resonance phenomenon that occurred in the hanger structural modal frequency when exposed to the rail corrugation, leading to the poor lateral vibration environment of the hanger and the fracture failure in the long-term service operation. The first-order structural modal frequency of the hanger is 432 Hz, which is very close to the wheel/rail excitation frequency of 435 Hz caused by the rail corrugation. The modal frequency of three newly designed hangers can prevent the frequency caused by the rail corrugation. Experimental verification of the new hangers showed a 55.49% lower maximum average acceleration of hanger lateral vibration compared to the original structure, confirming the effectiveness of the redesigned hangers.